(untitled) - Leach, James A. (Boston, 2006)
AutoCAD is the market leader for all CAD software and is used by nearly two million students and professionals in architecture, engineering, construction, and design. Leach's AutoCAD 2006 Instructor is designed to teach AutoCAD 2006 for instructor-lead and independent study, providing complete coverage of the features and capabilities of AutoCAD. Developed from teaching techniques used in an authorized AutoCAD Training Center and in instruction for engineering colleges, this command-oriented text is rich in pedagogy and engineering, architecture, design, construction, and manufacturing examples, making it suitable for a wide range of student learners. The chapters are structured in a practical sequence beginning with instruction in general procedures for using the computer interface, setting up and creating drawings, and then progressing to advanced features such as dimensioning, special drawing applications and AutoCAD features, three-dimensional modeling and rendering, and software customization.
Keywords: Computer graphics,AutoCAD